Perspectives of education sector stakeholders on a teacher training module to reduce HIV/AIDS stigma in Western Kenya - Ashley Chory; Winstone Nyandiko; Whitney Beigon; Josephine Aluoch; Celestine Ashimosi; Dennis Munyoro; Michael Scanlon; Edith Apondi; Rachel Vreeman (BMC, 2021)
Abstract Background For adolescents living with HIV (ALWH), school may be the most important but understudied social sphere related to HIV stigma. Teachers are role models in the classroom and within the community, and their attitudes and behavior towards people living with HIV may have critical psychosocial and treatment ramifications. Altering teachers' knowledge, attitudes and beliefs (K/A/B) about HIV could reduce the stigmatizing content within their teaching, classrooms and school, improving the environment for ALWH. Methods We developed a one-day teacher training module to enrich teacher K/A/B that included lecture presentations, HIV films and educational animation, structured instructions for teacher role play scenarios, and a question-and-answer session facilitated by a trained ALWH peer educator. We also conducted key informant interviews with education sector subject matter experts (SMEs), including education officers, county commissioners and head teachers to review and provide feedback on the teacher training module. Results We assembled an adolescent community advisory board and recruited 50 SMEs to review the training module and provide feedback. All SME participants stressed the importance and need for interventions to reduce stigma in the classroom, highlighting their own experiences observing stigmatizing behaviors in the community. The participants perceived the training as culturally relevant and easy to understand and had minor suggestions for improvement, including using image-based resources and brighter colors for ease of reading. All participants thought that the training should be expanded outside of the schools, as all people in a community have a role in the reduction of HIV stigma, and offered suggestions for other settings for implementation. Conclusion Data from interviews with education sector stakeholders demonstrate that our process for developing a culturally appropriate multi-media intervention to reduce HIV stigma in the schools was feasible.